Can Visual Acuity Be Reliably Measured at Home? Validation of Telemedicine Remote Computerised Visual Acuity Measurements - Ailsa Ritchie; Silva Atamian; Nilpa Shah; Alistair Laidlaw; Christopher Hammond (British and Irish Orthoptic Journal, 2021)
Purpose: The recent pandemic has identified the need for telemedicine assessment of ophthalmology patients. A vital component of such assessment is visual acuity (VA) measurement. The aim of this study was to determine the feasibility and reliability of computerised ‘at home’ VA measurements using COMPlog software. Methods: A Bland Altman method comparison study of worse eye ‘in clinic’ and ‘at home’ orthoptist-supervised COMPlog computerised VA measurements. Subjects underwent gold standard semi-automated computerised test and retest logMAR VA measurements on their habitually corrected worse eye both ‘in clinic’ and ‘at home.’ The orthoptist ran the test from the eye clinic with the patient viewing a secondary PC monitor either in the same clinic room or at home. A screen sharing voice and video conferencing application and standard consumer IT hardware were employed to present the test optotypes in the patient’s home. Results: 23 paediatric and 13 adult patients with a range of ocular diseases and worse eye visual acuities were included (range –0.14 to 1.06 logMAR). No significant bias was found between ‘in clinic’ and ‘at home’ measurements (mean –0.01 logMAR and 95% confidence interval –0.03, 0.00 logMAR). Test-retest variability of ‘in clinic,’ ‘at home’ and ‘in clinic’ versus ‘at home’ measurements were within normal reported ranges at 0.12 logMAR (6 ETDRS letters) or less. Conclusion: Remote home VA testing performed by an eye care professional using a semi-automated VA measurement program and video conferencing application provided unbiased measurements with acceptable test-retest reliability. Home testing was both feasible and acceptably reliable in appropriately equipped patients.